2002
DOI: 10.1177/019874290202800104
|View full text |Cite
|
Sign up to set email alerts
|

Replication of the First Step to Success Model: A Multiple-Case Study of Implementation Effectiveness

Abstract: The First Step to Success program was implemented with 22 kindergartners who showed early signs of developing antisocial behaviors, and it was completed by 16 of the children. All 16 children showed significantly increased levels of academic engaged time after completing the program, with follow-up levels generally maintained at acceptable levels. Overall behavioral improvement, as measured by the Child Behavior Checklist (CBCL), was significant but variable. The improvement shown on the CBCL by the first coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
(14 reference statements)
4
17
0
2
Order By: Relevance
“…Diken and Rutherford (2005) also indicated that teachers and parents had positive feedback about the effects of the program on children, noting positive changes in terms of undesired behaviors and high satisfaction with the program among teachers. In another study, Overton et al (2002) similarly observed positive behavior changes in the target children such as controlling behaviors, calmness, and being patient, getting on well with peers after the program, and that they were happy with the program.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Diken and Rutherford (2005) also indicated that teachers and parents had positive feedback about the effects of the program on children, noting positive changes in terms of undesired behaviors and high satisfaction with the program among teachers. In another study, Overton et al (2002) similarly observed positive behavior changes in the target children such as controlling behaviors, calmness, and being patient, getting on well with peers after the program, and that they were happy with the program.…”
Section: Discussionmentioning
confidence: 79%
“…In a study conducted by , teachers indicated that they had observed positive changes both in their own behaviors and in the behaviors of other students after the implementation of the program. The interviews conducted by Overton et al (2002) with the teachers after the implementation of the intervention program revealed that the teachers learned positive teaching strategies thanks to the program; they became more patient toward children, limited children less, reinforced positive behaviors, and developed good communication skills with children. In other studies about the program it was found that it had promoted a positive change in teachers' own behaviors, and through this, the interaction(s) between the teacher, the target student, and other students developed in a positive way, and the teacher applied positive teaching approaches more frequently (Diken & Rutherford, 2005;Golly et al, 2000;Overton et al, 2002;Özdemir, 2011;Walker, Kavanagh, et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Başka bir deyişle, bireyin başlangıçta içerisinde bulunduğu çevreye uyum sağlamada yaşadığı birtakım antisosyal davranışlar zamanla okulu terk etme, okuldan kaçma, şiddete yönelme, hırsızlık, uyuşturucu ve ilaç kullanımı gibi sonradan müdahale edilmesi zor olan ve iyileştirilmesi uzun zaman alan kalıcı davranış problemlerine dönüşebilmektedir (Beard ve Sugai, 2004;Diken ve diğ., 2008;Overton, McKenzie, King ve Osbourne, 2002;Sprague ve Perkins, 2009). Buna ek olarak, bu konuda sayısız bilimsel çalışmalar gerçekleştiren araştırmacılar antisosyal davranış sergileyen çocukların uygun eğitim almadıkları durumlarda bu çocukların problemlerinin ergenlik yıllarına, hatta bireyin yetişkinlik yıllarına da yansıyacağını ve toplumda istenmeyen bireyler olabileceklerini vurgulamaktadırlar Walker, Kavanagh ve diğ.,, 1998;Walker ve diğ., 2009).…”
unclassified
“…Step to Success early intervention program was initially developed in 1992 and has been extensively evaluated using multiple research designs, including single subject (Carter, & Homer, 2007, 2009Golly, Sprague, Walker, Beard, & Gorham, 2000;Overton, McKenzie, King, & Osborne, 2002;Sprague, & Perkins, 2009), longitudinal (Nelson et aI., 2009;Walker et aI., 1998), quasi-experimental (Diken, & Rutherford, 2005;, and experimental (Walker et aI., 2005;Walker et aI., 2009). These evaluations have demonstrated strong, positive classroom effects across the majority of the at-risk primary level elementary school children with moderate or emerging behavioral disorders that were treated.…”
Section: The Firstmentioning
confidence: 99%